Olympiodorus of Alexandria : Exegete, Teacher, Platonic Philosopher - Joosse, Albert (Philosophia Antiqua, 2021)
This is the first collected volume dedicated to the work of the 6th-century CE philosopher Olympiodorus of Alexandria. His Platonic commentaries are rare witnesses to ancient views on Plato's Socratic works. As a pagan, Olympiodorus entertained a complex relationship with his predominantly Christian surroundings. The contributors address his profile as a Platonic philosopher, the ways he did and did not adapt his teaching to his Christian audience, his reflections on philosophical exegesis and communication and his thinking on self-cognition. The volume as a whole helps us understand the development of Platonic philosophy at the end of antiquity.